1991
DOI: 10.1080/00140139108967336
|View full text |Cite
|
Sign up to set email alerts
|

Occupational musculoskeletal disorders in the neck and upper limbs of forestry workers exposed to hand-arm vibration

Abstract: An epidemiologic and clinical study of neck and upper limb musculoskeletal disorders was carried out on 65 vibration-exposed forestry operators using chain-saws and 31 comparable control subjects (maintenance workers) performing manual activity and not exposed to vibration. Upper limb function was evaluated by measuring finger and wrist circumference size, maximal hand grip strength and range of motion manoeuvres in both the controls and the exposed workers. Vibration from two chain-saws was measured, and vibr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
71
0
3

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(80 citation statements)
references
References 14 publications
6
71
0
3
Order By: Relevance
“…The reproducibility of the diagnosis was demonstrated for 4 of the studies (18,35,37,38) and suggested in 2 others (39,63). Blinded assessment of outcome was explicitly declared in 5 studies (18,35,37,43,61), but may have occurred in several others by virtue of design or previously described methodology (19,38,58,65).…”
Section: General Findingsmentioning
confidence: 99%
See 3 more Smart Citations
“…The reproducibility of the diagnosis was demonstrated for 4 of the studies (18,35,37,38) and suggested in 2 others (39,63). Blinded assessment of outcome was explicitly declared in 5 studies (18,35,37,43,61), but may have occurred in several others by virtue of design or previously described methodology (19,38,58,65).…”
Section: General Findingsmentioning
confidence: 99%
“…In 14 of the 21 reports, the analysis was principally carried out through a comparison of job titles, but, in 11 studies, physical exposures were objectively characterized to a varying extent (18,37,(39)(40)(41)(42)(43)(61)(62)(63)(64). Several studies offered exposure-response information by quantified level of exposure (18,37,61,62) or time worked in the job (35,38,41), but in others only crude and sometimes composite exposure variables were used. Three studies analyzed the interaction between physical exposures (18,37,43).…”
Section: General Findingsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 14 articles described significant differences in the occurrence of CTS between occupations, the OR values ranging from 1.86 to 76.5 (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32). In eight studies, no significant differences were observed, the OR values ranging from 0.91 to 1.63 (33)(34)(35)(36)(37)(38)(39)(40).…”
Section: Job Title and Carpal Tunnel Syndromementioning
confidence: 99%